Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.2298/gensr1401269a
|View full text |Cite
|
Sign up to set email alerts
|

Study on genetic variability in MHC-DRB1 second exon in Makuie sheep breed population

Abstract: In the present study polymorphism of the exon 2 of MHC (Major Histocompatibility Complex) gene in Makuie sheep breed was studied. Genomic DNA from blood samples of 90 sheep was extracted and a 279 bp MHC exon 2 fragment was amplified using polymerase chain reaction (PCR). PCR products were subjected to enzymatic digestion using RsaI endonuclease. Digested PCR products were electrophoresed on 2% agarose gel. The results showed the existence of 10 alleles: A, B, E, F, I, M, O, P, Q and V for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A particular focus of the study is the abomasal GIN Haemonchus contortus and was justified by this parasite’s ability to produce large numbers of eggs, resulting in extensive pasture contamination; the blood-sucking nature of this nematode, which can causes life-threatening levels of anemia; and the associated potential for very significant reductions in lamb performance and survival ( Gatongi et al, 1998 ; Waller et al, 2004 ). In Iran, Ashrafi et al (2014) demonstrated polymorphism in exon 2 of MHC gene OLA-DRB1 in the Makui sheep breed of Northwestern Iran. In this study, our aim was thus to explore possible associations between nematode resistance and polymorphism of DRB1.…”
Section: Introductionmentioning
confidence: 99%
“…A particular focus of the study is the abomasal GIN Haemonchus contortus and was justified by this parasite’s ability to produce large numbers of eggs, resulting in extensive pasture contamination; the blood-sucking nature of this nematode, which can causes life-threatening levels of anemia; and the associated potential for very significant reductions in lamb performance and survival ( Gatongi et al, 1998 ; Waller et al, 2004 ). In Iran, Ashrafi et al (2014) demonstrated polymorphism in exon 2 of MHC gene OLA-DRB1 in the Makui sheep breed of Northwestern Iran. In this study, our aim was thus to explore possible associations between nematode resistance and polymorphism of DRB1.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods have been used to study genetic variation in the PRLR gene in various birds and animals. Among different methods, PCR-SSCP analysis has been found a valuable technique in identifying genetic variation of the PRLR gene in farm animals (KONNAI et al, 2003;GRUSZYNSKA et al, 2005, ASHRAFI et al, 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers link the genes in the sheep major histocompatibility complex (MHC) with the ability of sheep to resist infection by GIN as measured by feacal egg count (FEC) and revealed polymorphisms in exon 2 and adjoining intron 2 of the expressed gene DRB1. The DRB1 exon 2 encodes 1 domain, which constitutes part of the protein binding receptor (PBR) or T-cell receptors of the DR molecules and is likely to be related to functionality such as disease resistance/susceptibility (Paterson et al, 1998;Charon et al, 2002;Ashrafi et al, 2014 andValilou et al, 2015). The DR genes are highly polymorphic in nature and proteins encoded by these genes are expressed in elevated concentrations, specifically on the cell membranes of macrophages and B cells (Outteridge et al, 1996).…”
Section: Introductionmentioning
confidence: 99%